Neurological Complications Associated with Respiratory Syncytial Virus Infections: A Scoping Review of Prospective Clinical Trials Conducted in Populations up to 17 Years of Age - Aikaterini S. Stravoravdi; Xanthippi Topalidou; Georgios Papazisis (Pathogens)
Objective: This study aimed to review the neurologic and cognitive complications of respiratory syncytial virus (RSV) infections through studies involving infants, children, and adolescents up to 17 years of age. Methods: The PubMed, Scopus, Cochrane Library, and PsycINFO databases were comprehensively searched for prospective clinical trials written in the English language that assess the neurologic and/or cognitive complications of RSV. This review was conducted according to the recommendations of the PRISMA-ScR checklist. Results: The vast majority of studies have concentrated on younger children, with limited investigation into long-term cognitive outcomes. While data on adolescents are sparse, this likely reflects the lower incidence of RSV-related neurological complications in this age group, rather than a critical gap in the research. The key findings from the 11 included studies highlighted a range of neurologic complications, which are particularly prevalent in children under six years of age. One study reported delayed language development and potential memory impairments, highlighting the virus’s potential impact on early cognitive processes. Conclusions: The findings of this review highlight the need for more clinical studies focusing on the impact of RSV on the central nervous system and potential complications that may arise, particularly in groups at high risk of acquiring this infection. Future investigations should focus on longitudinal assessments to elucidate long-term effects and standardize methodologies for enhanced comparability.